2022
DOI: 10.1021/acs.nanolett.1c04809
|View full text |Cite
|
Sign up to set email alerts
|

Single-Atom Pt Anchored on Oxygen Vacancy of Monolayer Ti3C2Tx for Superior Hydrogen Evolution

Abstract: Two-dimensional (2D) MXene-loaded single-atom (SA) catalysts have drawn increasing attention. SAs immobilized on oxygen vacancies (O V ) of MXene are predicted to have excellent catalytic performance; however, they have not yet been realized experimentally. Here Pt SAs immobilized on the O V of monolayer Ti 3 C 2 T x flakes are constructed by a rapid thermal shock technique under a H 2 atmosphere. The resultant Ti 3 C 2 T x -Pt SA catalyst exhibits excellent hydrogen evolution reaction (HER) performance, inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
85
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(88 citation statements)
references
References 40 publications
3
85
0
Order By: Relevance
“…Ti 3 C 2 T x -Pt SA reduced the Gibbs free energy of hydrogen adsorption and exhibited superior electrocatalytic activity for the HER. 126 5.1.2 Heteroatomic bonding. MXene-doped heteroatom bonding with noble metals is a simple and effective strategy for anchoring noble metal single atoms.…”
Section: Vacancy Defect Anchoringmentioning
confidence: 99%
“…Ti 3 C 2 T x -Pt SA reduced the Gibbs free energy of hydrogen adsorption and exhibited superior electrocatalytic activity for the HER. 126 5.1.2 Heteroatomic bonding. MXene-doped heteroatom bonding with noble metals is a simple and effective strategy for anchoring noble metal single atoms.…”
Section: Vacancy Defect Anchoringmentioning
confidence: 99%
“…110,111 Methods for preparing single-atom site catalysts on MXenes usually refer to the replacement of the atom in the MXene structure by a metal single-atom. [112][113][114] The metal single-atom sites in the lattice of an MXene could result in a redistribution of the electronic structure, which leads to an improved electron environment for catalyzing the HER. Wang et al reported the preparation of double transition metal MXene nanosheets with abundant surface Mo vacancies (Mo 2 TiC 2 T x VMo) by electrochemical exfoliation (Fig.…”
Section: Sascs Based On Mxenesmentioning
confidence: 99%
“…Zhang et al reported a rapid thermal shock method to achieve the anchoring of Pt single-atom sites on the oxygen vacancies (O vac ) of monolayer Ti 3 C 2 T x flakes under a H 2 atmosphere. 114 Besides the HER, MXene-supported SASCs have also been applied in organic catalysis. 110 Chen et al achieved the anchoring of Pt atoms by utilizing the reducibility of Ti 3 C 2 MXene itself and the abundant Ti defects on its surface.…”
Section: Sascs Based On Mxenesmentioning
confidence: 99%
“…[14] Though most studies focused on the thermal decomposition of MXenes in different atmospheres, including reducing (H 2 ), [15] oxidative (air and oxygen) [16] and inert gases (nitrogen and argon), [17] their chemical reactivity with solutions (or during liquid processing) and solid agents at high temperatures was also evaluated. [18] From the perspective of practical application, several temperature-dependent properties (such as electrical conductivity [15] and mechanical strength [19] ) were taken into consideration as well. Apart from the above-mentioned stability-relevant properties, the energy conversion capabilities of MXenes, mainly based on photothermal and electrothermal effects, have been demonstrated to effectively transform solar irradiation and electricity into thermal energy.…”
Section: Introductionmentioning
confidence: 99%
“…The thermal stability of MXenes in general have sparked concern among material scientists trying to deal with certain urgent issues, such as the global energy shortage, based on these novel nanomaterials [14] . Though most studies focused on the thermal decomposition of MXenes in different atmospheres, including reducing (H 2 ), [15] oxidative (air and oxygen) [16] and inert gases (nitrogen and argon), [17] their chemical reactivity with solutions (or during liquid processing) and solid agents at high temperatures was also evaluated [18] . From the perspective of practical application, several temperature‐dependent properties (such as electrical conductivity [15] and mechanical strength [19] ) were taken into consideration as well.…”
Section: Introductionmentioning
confidence: 99%